Philosophy after Auschwitz in Th. Adorno: negative metaphysics - Berrio Peña, Arlex (Estudios de Filosofía, 2019)
This article is based on Adorno’s reflections on a new idea of philosophy developed in Negative Dialectics, specifically in the section “Meditations on Metaphysics”. In this passage, the author develops a critique of the categories of traditional metaphysics that serve as the basis for the philosophical proposal of the Enlightenment, both in Kant and Hegel. Adorno considers that philosophy has been an accomplice of barbarism in history. In this way, Auschwitz as a new category of analysis and metaphorical expression of irrationality and barbarism that destroys the human and the natural environment, allows the exercise of reflection. For this reason, for Adorno it is urgent to rethink philosophy after Auschwitz to prevent new forms of terror from repeating themselves. A new idea of metaphysics with a horizon of understanding,intervention, transformation and resignification is put forward. In short, a negative metaphysics that is directed towards what has been discarded by the traditional rationality.